2018
DOI: 10.1007/s11084-018-9555-8
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl Phosphate as a Primordial Energy Currency at the Origin of Life

Abstract: Metabolism is primed through the formation of thioesters via acetyl CoA and the phosphorylation of substrates by ATP. Prebiotic equivalents such as methyl thioacetate and acetyl phosphate have been proposed to catalyse analogous reactions at the origin of life, but their propensity to hydrolyse challenges this view. Here we show that acetyl phosphate (AcP) can be synthesised in water within minutes from thioacetate (but not methyl thioacetate) under ambient conditions. AcP is stable over hours, depending on te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 119 publications
2
96
0
Order By: Relevance
“…To answer this biological insight on different species and pathways is crucial [85]. In order to find out if energy coupling was necessary for life's first steps (still a subject of debate) several alternative energy currencies have been proposed and tested, for instance high-energy phosphates [86] or thioesters [87]-as it is known that cells use both, often sequentially (e.g., the production of ATP is sometimes mediated by thioesters). From there, further questions emerge: how did these energy-storing molecules become coupled and implemented into life as we know it (or: what was the order of entry of such heteroatoms as nitrogen, sulfur and phosphorus into proto-life's chemistry)?…”
Section: Pressing Questions In Ool Are Interdisciplinarymentioning
confidence: 99%
“…To answer this biological insight on different species and pathways is crucial [85]. In order to find out if energy coupling was necessary for life's first steps (still a subject of debate) several alternative energy currencies have been proposed and tested, for instance high-energy phosphates [86] or thioesters [87]-as it is known that cells use both, often sequentially (e.g., the production of ATP is sometimes mediated by thioesters). From there, further questions emerge: how did these energy-storing molecules become coupled and implemented into life as we know it (or: what was the order of entry of such heteroatoms as nitrogen, sulfur and phosphorus into proto-life's chemistry)?…”
Section: Pressing Questions In Ool Are Interdisciplinarymentioning
confidence: 99%
“…[12] Underh ydrothermalc onditions, the presence of thioacetate (formed in the presence of Fe/Ni-sulfides) [13] can also lead to the synthesis of Ac-P i which is am olecule relevant to metabolism. [14] Steep disequilibria across mineral membranes are thought to be significant for the emergence of metabolism in an alkaline vent setting, and since disequilibria-converting engines linked to ATP/ADP or PP i hydrolysis are essential for life, it has been suggested that analogous processes-though mineral-driven-may have been involved in thee mergence of metabolism. [15] Particularly the mineral green rust, am ixed valence iron oxyhydroxide, has been proposed to serve variousp rebiotic functions as an engine, electron transfer agent,a nd catalyst for organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Among these metabolites, acetylphosphate can phosphorylate biologically signi cant substrates in a way similar to ATP, promoting the origin of metabolism. [32] Coenzyme A is mainly involved in the metabolism of fatty acids and pyruvate, which can stimulate the tricarboxylic acid (TCA) cycle and provide 90% of the energy needed for the body's life. [33] Palmitic acid diets can cause lipotoxicity and energy metabolism imbalance in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%